2016
DOI: 10.4274/jcrpe.2313
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Neck Circumference and Non-Alcoholic Fatty Liver Disease in Childhood Obesity

Abstract: Objective:The aim of this study was to establish the association between anthropometric parameters and non-alcoholic fatty liver disease (NAFLD) and to determine the most reliable measurement as a parameter in predicting NAFLD.Methods:Two-hundred fifty-three obese children of ages 10 to 18 years were enrolled in this study. Anthropometric data and metabolic parameters such as fasting blood glucose, insulin and lipid levels, were measured. Liver function tests were assessed. NAFLD was determined by ultrasound.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…In anthropometric terms, all participants were above the cut-off point for waist circumference, with 20% being overweight and the other obese, with BMI mean values significantly higher for those of G1-NAFLD. In this study, there was a significant difference between the groups for neck circumference, and in BMI and waist circumference for G1-NAFLD, and our data are consistent with the study of Hatipoglu et al 9 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In anthropometric terms, all participants were above the cut-off point for waist circumference, with 20% being overweight and the other obese, with BMI mean values significantly higher for those of G1-NAFLD. In this study, there was a significant difference between the groups for neck circumference, and in BMI and waist circumference for G1-NAFLD, and our data are consistent with the study of Hatipoglu et al 9 .…”
Section: Discussionsupporting
confidence: 93%
“…The anthropometric variables most associated with NAFLD were higher body mass index (BMI) and waist circumference above the reference standard which is an indicative of visceral adiposity 9 . Dietary indicators highlight excessive calorie intake and a high proportion of carbohydrates about total caloric intake 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each participant was required to fill up a questionnaire providing detailed demographic characteristics, lifestyle risk factors and other information, while anthropometric data was measured by trained staff according to the unified standards [ 19 , 20 ]. Height and weight were measured with light clothing and without shoes, after emptying of bladder.…”
Section: Methodsmentioning
confidence: 99%
“…There are limited studies regarding the association between NC and NAFLD, and most of them deal only with adult populations. However, the few studies performed in child population with obesity have shown positive correlations, with differences between male and female genders [17][18][19].…”
Section: Introductionmentioning
confidence: 98%